Environmental life cycle assessment for a large-scale gold mining (2020)
Mining, generally speaking, is an industry which consumes water in an intensive way, and when metal fineness is less and more mineral is extracted, it will also increase the consumption of this source. Just in the last 40 years the trends of world production of the mineral extractive, manufacturing and services industries have grown steadily. And in Peru, for example, it has reduced the total area of glaciers and fresh water in the coasts, where around 60% of the population lives. For that reason, it is necessary to assess the impact that this sector generates in order to identify those significant impacts where solutions can be proposed. Using the LCA software SimaPro, the assessment is focused on large scale gold mining by heap leaching, where it was obtained those processes that worst effects to the environment resulted to be processing, mainly, and leaching ins second place, as well as the most affected impact categories were: climate change, agricultural land occupation, water and metal depletion. On the other hand, another three different impact categories, terrestrial, freshwater and marine ecotoxicity, showed an inverse result which could be translated as a potential positive impact, however due to the inventory and data collected, the affirmation cannot be possible to sustain.